Targeting DLBCL by mutation-specific disruption of cancer-driving oncogenes - Heshmatpour, Najmeh; Kazemi, S. Maryam; Schmidt, Niklas D.; Patnaik, Sarita R.; Korus, Patrick; Wilkens, Bodo G. C.; Macarrón Palacios, Arturo (Frontiers in Genome Editing, 2024)
Diffuse large B cell lymphomas (DLBCL) are highly aggressive tumors. Their genetic complexity and heterogeneity have hampered the development of novel approaches for precision medicine. Our study aimed to develop a personalized therapy for DLBCL by utilizing the CRISPR/Cas system to induce knockouts (KO) of driver genes, thereby causing cancer cell death while minimizing side effects. We focused on OCI-LY3 cells, modeling DLBCL, and compared them with BJAB cells as controls. Analysis of whole exome sequencing revealed significant mutations in genes like PAX5, CD79B, and MYC in OCI-LY3 cells. CRISPR/Cas9-mediated KO of these genes resulted in reduced cancer cell viability. Subsequent single and dual gRNA targeting of PAX5 mutations inhibited proliferation specifically in OCI-LY3 cells. Moreover, dual gRNA targeting of PAX5 and MYC induced chromosomal rearrangements, reducing cell proliferation substantially. However, targeting single intronic mutations did not affect cell viability, highlighting the importance of disrupting protein function. Targeting multiple mutations simultaneously addresses intra-tumoral heterogeneity, and the transient delivery of CRISPR/Cas9 allows for permanent gene disruption. While challenges such as incomplete editing efficiency and delivery limitations exist, further optimization may enhance therapeutic efficacy. Overall, our findings demonstrate the efficacy of CRISPR/Cas9 in targeting oncogenic mutations, opening avenues for precision medicine in DLBCL treatment.